Gut mucosal immunomodulation by probiotic fresh cheese - Medici, Marta Graciela (2004)
Probiotic Fresh Cheese (PFC) is a suitable vehicle for the oral administration of Streptococcus thermophilus, Lactococcus lactis (lactic acid starter bacteria), Bifidobacterium bifidum, Lactobacillus acidophilus and L. paracasei (probiotic bacteria). PFC warrants adequate viability of the bacteria (60 days after manufacture) and protects against acidity in vitro. The aim of this work was to evaluate the effect of PFC on the mucosal immune response in vivo. BALB/c mice were fed for 2, 5 or 7 consecutive days with PFC (10 8cells/day/mouse). Mice fed with conventional balanced diet or with Control Fresh Cheese (CFC) were used as controls. The immune response (phagocytic activity of peritoneal macrophages, number of IgA+ producing cells in the small and large intestine and ratio of CD4+ and CD8+ T lymphocytes in the small intestine) was evaluated at the end of each feeding period. The presence of each probiotic bacterium and total PFC microflora as bacterial antigens in Peyer's patches or in immune cells associated with the villi of the small intestine or in nodules and crypts of the large intestine was determined by using fluorescein isothiocianate (FITC)-labelled bacteria. Histological preparations of the small and large intestine were performed 30min after the administration of FITC-labelled bacteria. A significant increase in the phagocytic activity of peritoneal macrophages, in the number of IgA+ producing cells and in the CD4+/CD8+ ratio was observed in the small intestine after 5 days treatment with PFC whereas no significant differences were observed in the large intestine. These values returned to control values 8d following PFC withdrawal. In the large intestine, no significant differences were observed respect to controls. FITC-labelled pure cultures of B. bifidum and L. paracasei were identified mainly in Peyer's patches (small intestine) whereas L. acidophilus was mainly located in the large intestine. CFC microflora was found in lower levels than PFC microflora. This study demonstrates that PFC is a dairy product that enables Bifidobacterium bifidum, Lactobacillus acidophilus and L. paracasei to exert important immunomodulating effects in the gut.